Leishmaniasis in Santa Ana, Ecuador: knowledge assessment and control strategies - Guerrero, Lady M.; Briones, Gabriela M.; Briones, Boris A.; Merino, José M.; Cordero, Raúl A.; Alejandro, Carlos R. (Revista Gregoriana de Ciencias de la Salud, 2025)
Leishmaniasis is a parasitic disease transmitted by the bite of infected sand flies, with a high incidence in tropical areas, such as Santa Ana, Ecuador. This study aimed to analyze the community’s level of knowledge and the effectiveness of control strategies implemented in the region. A descriptive cross-sectional study was conducted with 25 residents, who completed surveys that collected sociodemographic data, knowledge about the disease, perceptions of preventive measures, and attitudes toward possible infection. Results showed that 92% of respondents were unaware of the disease, and 100% were unaware of its mode of transmission. Additionally, 68% considered preventive actions insufficient, and 64% perceived awareness campaigns as ineffective. Despite this, 80% expressed a willingness to seek hospital care in the event of suspicious symptoms. The study concludes that the persistence of leishmaniasis in the community is associated with a lack of information and a limited understanding of institutional efforts, highlighting the need to strengthen educational strategies, improve access to healthcare services, and expand community-based prevention campaigns.